Respostas

2014-06-01T19:32:20-03:00
X^2 - 4x +4 = 0
delta = (-4)^2 - 4x1x4
             16 - 16 = 0

x = -(-4)/2.1
x = 4/2
x = 2
1 5 1
A melhor resposta!
2014-06-01T19:35:08-03:00
 x^{2} - 2x = 2x - 4
 x^{2} -2x - 2x + 4 = 0
 x^{2} -4x +4 = 0

a= 1
b=-4
c= 4

Vamos pela Bhaskara.

Resolvendo delta:
Δ=  b^{2} . 4ac
Δ=  (-4)^{2} - 4 . 1 . 4
Δ= 16 - 16
Δ= 0

Agora que já sabemos o valor de delta, a Bhaskara:
 \frac{-b +-  \sqrt{delta} }{2a}
 \frac{4 +- 0}{2}

 x^{'} =  \frac{4}{2}
 x^{'} = 2

 x^{''} =  \frac{4}{2}
 x^{''} = 2
2 5 2